Proximal Decision Analysis - Howard, Ronald A. (Management Science, 1971)
This paper presents simplified techniques for analyzing the effect of uncertainty in large decision problems. Starting with the development of approximate expressions for the moments of a value lottery, we show that the probabilistic assessments of jointly related random variables necessary for these approximations are quite reasonable in number. The concepts of risk aversion, certain equivalent, and exponential utility function then permit writing useful approximations for the certain equivalent of the value lottery. Deterministic sensitivity analyses are described first for the case when the decision variables are fixed and then for the case when they can be changed to compensate for variations in state variables. The approximate effect and value of clairvoyance (revelation of ultimate values of uncertain variables) is derived from the original probabilistic assessment and the results of the deterministic sensitivity analysis. We next determine the approximate value of wizardry (changing uncertain variables into decision variables). The amount by which decision variables must be adjusted to account for risk aversion is established from earlier results. The final portion of the paper discusses a simple economic example that illustrates the application of the development.